Dealing with Dutch Disease - Brahmbhatt, Milan; Canuto, Otaviano; Vostroknutova, Ekaterina (World Bank, Washington, DC, 2012)
This note looks at so-called Dutch disease, a phenomenon reflecting changes in the structure of production in the wake of a favorable shock (such as a large natural resource discovery, a rise in the international price of an exportable commodity, or the presence of sustained aid or capital inflows). Where the natural resources discovered are oil or minerals, a contraction or stagnation of manufacturing and agriculture could accompany the positive effects of the shock, according to the theory. The note considers channels through which such natural resource wealth can affect the economy. It also focuses on the development implications of Dutch disease, particularly the potential negative effects related to productivity dynamics and volatility; and concludes with a summary of possible policy responses, including the mix of fiscal, exchange rate, and structural reform policies.